Successful management of persistent lower extremity lymphedema with suction-assisted lipectomy - John P. Micha; Dung H. Nguyen; Bram H. Goldstein (Elsevier, 2018)
Introduction: Lower-extremity lymphedema is a significant complication attributed to gynecologic cancer surgery, potentially effectuating severe edema and discernible pain. Case report: We report on a patient who developed persistent, lower-extremity lymphedema following her treatment for cervix cancer. Despite repeated efforts to manage the lymphedema with conventional measures, the patient's condition had not markedly improved. Thereafter, she underwent a suction-assisted lipectomy that effectively resolved her symptoms. Conclusion: Since lymphedema often remains disabling and incurable following traditional therapy, suction-assisted lipectomy should be considered as an alternative when endeavoring to optimally manage this complication.